Literatur Review : Ekonomi Kreatif Digital Sebagai Pilar Baru Pertumbuhan Nasional - Arta Uli Sianturi; Felicia Isabel Sihombing (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2024)
The digital creative economy has become one of the main pillars in driving national economic growth in the era of digital transformation. Based on the utilization of information and communication technology, this sector is able to create added value through innovation, creativity, and the utilization of superior human resources. This study aims to examine the role of the digital creative economy in supporting national economic development, by highlighting the contribution of this sector to increasing GDP, creating jobs, and strengthening global competitiveness. Through a descriptive qualitative approach and secondary data analysis, it was found that sub-sectors such as games, animation, graphic design, digital content, and ecommerce have experienced significant growth in the last decade. The success of the development of the digital creative economy also depends heavily on the support of government policies, an inclusive digital ecosystem, and the readiness of technological infrastructure. Thus, the digital creative economy is not only a complement to the national economic system, but has become a potential main driver in creating sustainable and equitable economic growth. Synergy between stakeholders is needed to optimize the potential of this sector as a new foundation for national growth in the future